Adjusters and Casualties: The Anatomy of Labor Market Displacement - Eric A. Hanushek; Simon Janssen; Jacob D. Light; Lisa Simon (Institute of Labor Economics (IZA), 2025)
We analyze the full distribution of displaced workers' earnings losses using a new method that combines matching and synthetic control group approaches at the individual level. We find that the distribution of earnings losses is highly skewed. Average losses, as estimated by conventional event studies, are driven by a small number of workers who suffer catastrophic losses, while most recover quickly. Observable worker characteristics explain only a small fraction of the variance in earnings losses. Instead, we find substantial heterogeneity in earnings losses even among workers displaced by the same firm who have identical observed characteristics such as education, age, and gender. Workers with minimal earnings losses adjust quickly by switching industries, occupations, and especially regions, while comparable workers with catastrophic losses adjust slowly, even though they are forced to make comparable numbers of switches in the long run.
Keywords: J24; J64; O30; 330; synthetic control groups; distributions of treatment effects; displacement losses